Heat integration analysis and optimization for a post combustion CO2 capture retrofit study of SaskPower's Shand Power Station. (May 2019) - Giannaris, Stavroula; Jacobs, Brent; Srisang, Wayuta; Bruce, Corwyn; Janowczyk, Dominika
Highlights: Steam extraction to the reboiler is optimized by inserting a butterfly valve in the IP-LP crossover downstream of the steam extraction point. Steam throttling at reduced power plant loads maintains sufficient energy flow to the reboiler for continued capture operations at reduced loads. Recovering flue gas waste heat for condensate preheating reduces output losses. Increasing the operating temperature and pressure of the deaerator, maximizes the usage of waste heat for condensate preheating. Configuring condensate preheaters in series with the low-pressure feed water heaters eases transitioning between capture and non-capture mode. Abstract: Post-combustion CO2 capture processes require thermal energy (from steam) for amine regeneration. In coal-fired power stations, steam can be extracted from within the steam cycle – resulting in a power production penalty. Heat integration is the study of minimizing energy consumption while maximizing heat recovery; required for successful CCS retrofits. In October 2014, the world's first fully integrated carbon capture facility, SaskPower's Boundary Dam Unit 3 (BD3), went on line. Various modifications to the turbine and feed heating system at BD3 contributed greatly to overall project costs. Novel heat integration strategies can reduce these costs. SaskPower's Shand Power Station (Shand) is a 305 MW, single unit, subcritical, lignite coal-fired power plant producing approximately 1100 kg of CO2 /MWh. Shand's capacity is twice that of BD3's - an ideal candidate for a CCS scale-up project. Using the design of the BD3 facility as a basis, heat integration analysis of the existing steam cycle at Shand was conducted using GateCycle ™ with aims to minimize costly modifications to the feed heating system. A baseline model was built using Shand's heat balance and served as the design case. Configurations of steam extractions to the deaerator (DEA), extractions to the reboiler, and utilization of a flue gas cooler (FGC) working in conjunction with a condensate pre-heater (CPH) train were investigated. Optimization of steam extraction to the reboiler and a novel configuration of the condensate preheating train integrated within the LP feed heating system were also accomplished.